Penerapan Mobile Government Pada Monitoring Aktigitas Aparatur Sipil Negara Di Dinas Komunikasi dan Informatika Kabupaten Bandung Barat - Asep Id Hadiana; Faiza Renaldi (Jurusan Informatika Universitas Jenderal Achmad Yani, 2019)
The development of mobile and mobile technology has given the Government the opportunity to utilize Mobile Information and Communication Technology (M-ICT) to help facilitate daily administration and to provide better services to citizens, businesses and government institutions through the use of mobile technology. The number of cellular telephone users in Indonesia continues to grow and now it has reached 50.6 million customers. Therefore, the application of m-Government in Indonesia is an interesting material to be studied. There are many forms of services that can be provided by m-Government, one of which is service in government offices for stakeholders of the state civil apparatus. This research takes place in the Office of Communication and Information (Diskominfo), which is one part of the Regional Work Unit (SKPD) in West Bandung Regency, and focuses on the existence of monitoring activities of the State Civil Apparatus (ASN) in the SKPD. ASN always plays an important role in the daily activities of the government bureaucracy, therefore it is necessary to manage employee data in order to achieve quality assurance on employee performance. Diskominfo West Bandung Regency has a number of employees of approximately 150 employees spread in 3 fields. The use of M-Government technology is believed to be able to provide a necessity to resolve the challenges that must be overcome, one of which is the external office / city monitoring of the ASN Diskominfo. This research will build a m-Government application in Diskominfo, West Bandung Regency to monitor the activities of the state civil apparatus (ASN), which uses smart cellphones based on Android as its media.